2011
DOI: 10.1002/jat.1650
|View full text |Cite
|
Sign up to set email alerts
|

Effects of embryonic exposure to polychlorinated biphenyls on zebrafish (Danio rerio) retinal development

Abstract: Polychlorinated biphenyls (PCBs) are persistent environmental pollutants that affect embryonic development. The purpose of this study was to examine the effects of embryonic exposure to PCBs on early retinal development in zebrafish, Danio rerio. Zebrafish embryos were immediately exposed to different concentrations (0, 0.125, 0.25, 0.5, 1.0 and 2.0 mg) of PCBs per liter of medium at 28.5 °C. Embryos were assessed at 30, 48, 72 and 96  h post-fertilization (hpf) for changes in embryonic survival rate, developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 47 publications
(46 reference statements)
1
22
0
Order By: Relevance
“…Importantly, two of the three measures were significantly elevated when the ‘bouncing’ disk was present compared to its absence, suggesting that the ability to perceive the moving disk was not substantively affected in the PCB-exposed larvae despite the propensity for PCB exposure to target retinal development in zebrafish (Wang et al, 2012). Rather, it seems more likely that the avoidance defect on the BD assay resulted from an effect of PCB exposure on motor system development or on central processes involved in threat avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, two of the three measures were significantly elevated when the ‘bouncing’ disk was present compared to its absence, suggesting that the ability to perceive the moving disk was not substantively affected in the PCB-exposed larvae despite the propensity for PCB exposure to target retinal development in zebrafish (Wang et al, 2012). Rather, it seems more likely that the avoidance defect on the BD assay resulted from an effect of PCB exposure on motor system development or on central processes involved in threat avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…Although continuous exposure to 1 ppm A1254 has been shown to induce significant structural and functional retinal defects at 7 dpf (Wang et al, 2012; Zhang et al, 2015), it is clear from our VSA data that, with a short PCB-exposure window, larvae could see the ‘bouncing’ disk. They showed changes in mean swim speed and mean percent still that were indistinguishable from those shown by the controls suggesting that their ability to see the disk’s movement was similar to that of the control larvae.…”
Section: Discussionmentioning
confidence: 70%
“…Chronic exposure to the commercial PCB mixture Aroclor (A) 1254 and to individual congeners may induce significant developmental defects including cardiac, craniofacial, skeletal and retinal abnormalities in zebrafish embryos and larvae (Billsson et al, 1998; Grimes et al, 2008; Ju et al, 2012; Li et al, 2014; Olsson et al, 1999; Orn et al, 1998; Sisman et al, 2007; Wang et al, 2012). Continuous exposure to A1254 from immediately after fertilization until testing at 7dpf has also been found to disrupt performance on an optomotor assay consistent with impaired visual acuity (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There was a significant decrease in RBC, WBC and Haemoglobin count were seen in our present study .These changes were purely dependent on time and dose. A decrease in RBC, WBC and Hb values in Cyprinous carpio to Mercury have been reported by 21 . The accumulation of mercury in the liver showed structural damage in the liver.…”
Section: Wbc Countmentioning
confidence: 94%
“…Hematological changes on exposure to heavy metals like the impairments in hematological parameters, such as drop or elevation in Hb, RBC, and WBC have been reported. 21 Further they revealed that the study of the hematological parameters is used for the detection of physic-different stress pathological changes in conditions such as exposure to heavy metals. A decrease in the similar findings erythrocyte count indicates the worsening of an organism state and it is developing anaemia were observed in Puntius conchonius after mercury exposure of 2 to 3 week's duration by some workers found a significant decreased in total erythrocyte count, hemoglobin content, ©Pharmaceutical and Biological Evaluations leukocyte count in air breathing fish.…”
Section: Wbc Countmentioning
confidence: 99%